Barriers to Innovation and Innovative Performance of Portuguese Firms - Madeira, Maria Jose (2020)
This paper aims to identify and analyze the main limiting factors to innovation performance in terms of product and process innovation. The limiting factors to innovation, difficult the innovation process of a firm and consequently influence its innovation performance. Thus, it is intended with this essay to develop a theoretical support based on current reference approaches, corroborated by an empirical support which allows identifying and analysing the restraining factors of innovation activity and of innovation performance. The database is extracted from the Community Innovation Survey - CIS 2010, conducted under the responsibility of the Office of Planning, Strategy, Evaluation and International Relations/Ministry of Science, Technology and Higher Education (GPEARI/MCTES), in collaboration with the National Statistics Institute (INE), under the supervision of EUROSTAT. In order to identify the limiting factors to innovation performance a logistic regression model concerning the barriers to innovation is performed. The analysis suggests that several barriers to innovation have influence on the Innovative performance of Portuguese firms. These results may be due to the fact that the barrier of perception stimulates the firm to overcome these difficulties, promoting the internal propensity to innovate. The most important barriers perceived in the study are: high innovation costs, perceive uncertainties in the demand and the market for new goods and services and show a lack of qualified personnel to carry out innovation activities and a lack of market information are less likely to innovate than firms that do not experience these difficulties.